The Times : how the newspaper of record survived scandal, scorn, and the transformation of journalism - Nagourney, Adam (Crown, 2023)
"A sweeping behind-the-scenes look at the last four turbulent decades of "the paper of record," The New York Times, as it confronted world-changing events, internal scandals, and faced the existential threat of the internet For over a century, The New York Times has been an iconic institution in American journalism, one whose history is intertwined with the events that it chronicles--a newspaper read by millions of people every day to stay informed about events that have taken place across the globe. In The Times, Adam Nagourney, who's worked at The New York Times since 1996, examines four decades of the newspaper's history, from the final years of Arthur "Punch" Sulzberger's reign as publisher to the election of Donald Trump in November 2016. Nagourney recounts the paper's triumphs--the coverage of September 11, the explosion of the U.S. Challenger, the scandal of a New York governor snared in a prostitution case--as well as failures that threatened the paper's standing and reputation, including the discredited coverage of the war in Iraq, the resignation of Judith Miller, the plagiarism scandal of Jayson Blair, and the high-profile ouster of two of its executive editors. Drawing on hundreds of interviews and thousands of documents and letters contained in the newspaper's archives and the private papers of editors and reporters, The Times is an inside look at the essential years that shaped the newspaper. Nagourney paints a vivid picture of a divided newsroom, fraught with tension as it struggled to move into the digital age, while confronting its scandals, shortcomings, and swelling criticism from conservatives and many of its own readers alike. Along the way we meet the memorable personalities--including Abe Rosenthal, Max Frankel, Joe Lelyveld, Bill Keller, Jill Abramson, Dean Baquet, Punch Sulzberger and Arthur Sulzberger Jr.--who shaped the paper as we know it today. We see the battles between the newsroom and the business operations side, the fight between old and new media, the tension between journalists who tried to hold on to the traditional model of a print newspaper and a new generation of reporters who are eager to embrace the new digital world. Immersive, meticulously researched, and filled with powerful stories of the rise and fall of the men and women who ran the most important newspaper in the nation, The Times is a definitive account of the most pivotal years in New York Times history"--